2022
DOI: 10.1128/aac.00254-22
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Remdesivir and GS-441524 in Hospitalized COVID-19 Patients

Abstract: The objective of this study was to describe the population pharmacokinetics of remdesivir and GS-441524 in hospitalized coronavirus disease 2019 (COVID-19) patients. A prospective observational pharmacokinetic study was performed in non-critically ill hospitalized COVID-19 patients with hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Although the elimination rate was similar to that in our study, the larger CL and V may be attributed to the high BMI in the study population as the authors suggested. 11 The AUC of GS-441524 was in a similar range as previously reported. 6 In addition, these studies the relationship between GS-441524 exposure and renal function.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Although the elimination rate was similar to that in our study, the larger CL and V may be attributed to the high BMI in the study population as the authors suggested. 11 The AUC of GS-441524 was in a similar range as previously reported. 6 In addition, these studies the relationship between GS-441524 exposure and renal function.…”
Section: Discussionsupporting
confidence: 86%
“…In one study, 12 the CL and V of GS‐441524 were reported as 11.8 L/h (ISV = 26%) and 382 L (ISV = 34.5%), respectively, which were similar to our results (11.0 L/h [ISV = 43.0%] and 271 L [ISV = 58.1%], respectively). Another study 11 reported the CL and V of GS‐441524 in patients with COVID‐19 as 27.6 L/h (ISV = 47.4%) and 1060 L (ISV = 42.9), respectively. Although the elimination rate was similar to that in our study, the larger CL and V may be attributed to the high BMI in the study population as the authors suggested 11 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This might include currently available antivirals, such as molnupiravir or remdesivir ( 46 , 47 ), but other agents that have recently been approved in other settings such as ensitrelvir ( 48 ) or are under development, e.g. GS441525 ( 49 ), could also be considered. Ultimately, the route of administration, side effect profile, and drug-drug interactions will decide which antiviral, if efficacious, is optimal.…”
Section: Current State Of Long Covid Management and Potential Therape...mentioning
confidence: 99%